Contribution to the study of new integration rules on the level of Economic and Monetary of central Africa - (:unkn) unknown (My University, 2019)
After the failure of the UDEAC and common policies intended to achieve the customs union between the States of Central Africa, these latter are engaged to question all economic policies of integration adopted since their attainment of the international sovereignty. The analysis of causes of this failure led them not to abandon the Community ideal, but to revive it on new bases. In fact, the aim of this study is to put in light the changes and legal, political and socio-anthropological evolutions that meet the Economic and Monetary community of the Central Africa considered like our problematic, has emphasized it throughout this work as an effective barometer of the analysis of the new economic regionalism between the countries of central Africa. In spite of the multiple sectorial policies implemented by the common institution and which one will be able to measure the contribution to the integration of the economies of sub region only in medium or long term, the adoption and then the implementation of common new rules of integration governing the Common Market under setting-up between the Member States is a perfect illustration of the new choices made the sub region. Notably, those consisting in making common law as we have proved it from chapter to chapter the essential driving force of the realization of the Community objectives that they set themselves.
Keywords: African Research